Appropriateness of colonoscopy in a University Hospital - Tan, Yen Mei; Goh, Khean Lee (Malaysian Medical Association, 2004)
An open access endoscopy system allows for the direct scheduling of endoscopies by non-gastroenterologist physicians without prior gastroenterology consultation. The aim of our study was to examine our practice of open access endoscopy by evaluating the appropriateness of referrals for colonoscopy and to determine whether there were differences depending on the specialty of the referring clinician. The indication for colonoscopy was assessed in 499 consecutive outpatients referred for colonoscopy at University Hospital, Kuala Lumpur over a 12-month period. The American Society of Gastrointestinal Endoscopy (ASGE) guidelines were used to determine the appropriateness of referrals. 80.6% of colonoscopies requested by the gastroenterologist were performed for accepted indications compared to 50.6% of referrals by the primary care physician (p<0.001) and 67.0% of referrals by the surgeon (p=0.006). The rate of colonoscopies generally not indicated was 2.1% for the gastroenterologist, 25.0% for the internist (p=0.002) and 7.5% for the surgeon (p=0.04). The rate of indications not listed in the ASGE guidelines was significantly lower for requests made by gastroenterologists (17.3%) than those requested by primary care physicians (44.2%; p<0.001). Patients who have had prior consultation with the gastroenterologist were significantly more likely to undergo colonoscopy for appropriate indications than among patients who were referred through an open access system. The rate of inappropriate indications for colonoscopy was also significantly lower when the gastroenterologist made the referral. A substantial proportion of colonoscopies (25.4%) was performed for indications not listed in the ASGE guidelines.